The Effect of Workload, Work Stress, and Compensation on Employee Performance with Work Motivation As an Intervening Variable - Amrillah, Habib; Wahyuni, Sri; Rachmawati, Erny; Suyoto, Suyoto (Islamic Economics Journal, 2025)
This study aims to investigate the impact of work burden, work stress, and compensation on employee performance, with motivation serving as an intervening variable. This research employs a quantitative approach, using a method that collects data in the form of questionnaires, which are then converted into a Likert scale. In research, populations and samples are often discussed. There are 100 employees at LAZISMU Central Java, and the study employs saturated sampling, a type of non-probability sampling. Analysis method used in this study: SEMPLS (Structural Equation Modeling - Partial Least Squares). The study’s results indicate that workload has a significant effect on work motivation and employee performance, both directly and through work motivation as an intervening variable. The more precise the workload management, the higher the motivation and performance produced. In contrast, compensation and work stress have no significant effect, either directly or indirectly, on motivation and performance. These findings indicate that in a work environment like Lazismu Banyumas, employee performance is more influenced by internal factors and work values, such as the meaning of workload and motivational strength, rather than financial incentives or work pressure.